PENGARUH CORPORATE SOCIAL REPONSIBILITY TERHADAP RESPON INVESTOR DALAM SEKTOR INDUSTRI BARANG KONSUMSI - Jane, Merrie (Business Accounting Review, 2015)
Corporate Social Responsibility (CSR) has grown to be an integral part of corporate strategy. There were many researches done about the affect of CSR on investor response, but the results were inconsistent. The purpose of this research was to study the affect of CSR on investorâs response in Consumer Goods Industrial sector.CSR was measured by CSRI, meanwhile investor response was measured by CAR. ROA, firm size, DER, and market share were used as control variables. The sample of this research consisted of companies from Consumer Goods Industrial sector, which listed in Indonesia Stock Exchange during 2008-2012, with the total number of 115 firm years.The results proved that CSR had positive affect on investor response. ROA had a negative affect on investor response. Whereas, firm size, DER, and market share had no affect on investor response.